Topographies of the Obsolete: Vociferous Void - Mydland, Anne Helen; Brownsword, Neil (UK Topographies of the Obsolete Publications, 2013)
Topographies of the Obsolete is an artistic research project initiated by Neil Brownsword and Anne Helen Mydland at Bergen Academy of Art and Design (KHiB) in Norway in collaboration with partner universities/institutions in Denmark, Germany and the UK. The main collaborative partner, the British Ceramics Biennial, invited KHiB to work at the original Spode factory site in Stoke-on-Trent, to develop a site specific artistic response as a core element of their 2013 exhibition programme. The project focus centres upon the landscape of post-industry, with a particular emphasis upon Stoke-on-Trent, a world renowned ceramic capital that bears evidence of fluctuations in global fortunes.